Draft Annual Plan 2008-2009 Part-III Government of Sikkim - Planning Commission (Planning Commission, 2008)
It has been 12 years since the establishment of a separate Department of Sports and Youth Affairs in which time an administrative shape catering to the requirements of the department was given, A full fledged Administrative Staff with proper strength headed by the Head of the Department Exists An accounts division headed by The Accounts Officer along with the Accounts staffs functions. Coaches were posted to give proper coaching to the budding talents of the state. Physical Education Teachers have been absorbed from HRDD Two District Sports Officers presently man the two district sports centers, supported by alloted staffs, with a Deputy director in charge of the South /West districts. He is also declared as DDO of these two districts.
Development Planning, Economic Reforms & North - Eastern Council Affairs Department Government of Sikkim